2018
DOI: 10.1177/0146167218766857
|View full text |Cite
|
Sign up to set email alerts
|

(How) Does Initial Self-Control Undermine Later Self-Control in Daily Life?

Abstract: Past research suggests that self-control lapses occur more frequently following demanding experiences in daily life. However, the reason for these effects is debated. Three studies were therefore conducted to better understand self-control lapses. Exploratory analyses were conducted in Study 1 to identify possible effects. Studies 2 and 3 evaluated these effects' reliability. Two patterns were identified. First, initial desire-goal conflict predicted later increases in subjective fatigue. This was in turn rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 44 publications
3
16
0
Order By: Relevance
“…Indeed, the effects observed here in the appetitive domain are consistent with other studies that have showed reductions in activity in prefrontal cortex—and accompanying task deficits in various cognitive tasks—following self-control exertion (Friese et al, 2013; Luethi et al, 2016; e.g., Persson, Larsson & Reuter-Lorenz, 2013). The present findings are also consistent with predictions made by models emphasizing the role of self-regulatory fatigue in affecting self-control outcomes (Evans, Boggero & Segerstrom, 2015; Hofmann et al, 2012; Wilkowski et al, 2018), and those that highlight the limitations of cognitive control processes more broadly (Shenhav et al, 2017).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Indeed, the effects observed here in the appetitive domain are consistent with other studies that have showed reductions in activity in prefrontal cortex—and accompanying task deficits in various cognitive tasks—following self-control exertion (Friese et al, 2013; Luethi et al, 2016; e.g., Persson, Larsson & Reuter-Lorenz, 2013). The present findings are also consistent with predictions made by models emphasizing the role of self-regulatory fatigue in affecting self-control outcomes (Evans, Boggero & Segerstrom, 2015; Hofmann et al, 2012; Wilkowski et al, 2018), and those that highlight the limitations of cognitive control processes more broadly (Shenhav et al, 2017).…”
Section: Discussionsupporting
confidence: 90%
“…Most recently, the consensus appears to be that the available evidence, in favor of and/or against self-regulatory depletion effects, is inconclusive (Friese et al, 2018). However, a recent pre-registered study with large samples (Ns ≥ 377) has shown reliable effects consistent with an attentional-based account of depletion (Garrison, Finley & Schmeichel, 2018), and studies using more ecologically valid designs have provided supporting evidence for the role of self-regulatory fatigue in precipitating self-control failures in daily life (Hofmann et al, 2012; Wilkowski et al, 2018), suggesting, perhaps, that focusing on more ecologically valid and appetitive behaviors (such as dieting failures) may provide better traction on the underlying phenomena.…”
Section: Introductionmentioning
confidence: 99%
“…We now wonder, though, if conflict has been overemphasized, if the near exclusive focus on conflict by many models has been to the field's detriment. We ask because new work suggests that the biggest drag on goal attainment is not the inability to resolve conflict (i.e., lack of self-control), but the presence of conflicting desires and temptations to begin with (Milyavskaya & Inzlicht, 2017; see also, Wilkowski, Ferguson, Williamson, & Lappi, 2018). Once conflict is present, in other words, successful self-control in the moment does not necessarily translate to successful self-regulation in the end.…”
Section: Conflictmentioning
confidence: 99%
“…Along the same lines, Wilkowski, Ferguson, Williamson and Lappi (2018) conducted an experience-sampling study on self-control in which they found that earlier exertion of self-control led to more enactment of later desires. However, this increase in desire enactment was not due to failure to exert self-control, but rather the absence of later self-control attempts.…”
Section: Mood-repairmentioning
confidence: 99%
“…Put simply, individuals were unwilling rather than unable to exert self-control following earlier self-control effort. Accordingly, the pursuit of momentary pleasure was a matter of choice rather than a lapse in volitional control (Wilkowski et al, 2018).…”
Section: Mood-repairmentioning
confidence: 99%